An integrated model to explain sustainable consumption behaviour - Chuah, Cindy * (2022)
Extant attitudinal studies on sustainable consumption suggest that individual’s sustainable consumption behaviour has been researched extensively from the perspective of individual’s cognition and has neglected other aspects that could also lead to attitude formation, such as the affective, behavioural, and normative dimensions of responses. This incomplete conceptualization of attitude may lead to the inconsistency in predicting one’s behaviour. Besides considering the various responses in attitude formation, it is also important to include the antecedents of those responses to address the lack of conceptualization and operationalization of attitude construct as pointed out by Bagozzi (1979). Thus, the theory of appraisal which is known for its significant effect in regulating a person’s action tendencies, physical responses, behaviour, and feelings is included in the research framework. The sustainable consumption behaviour is measured using the model of goal directed behaviour. Therefore, taking into consideration the promising effect of each of the components (appraisal, various attitudinal responses, and behaviour) towards attitude-behaviour consistency, this study aims to examine the integrated effect of cognitive and affective appraisal, various responses, and attitude, as well as the interactive effect of affective, behavioural, and normative response in the context of sustainable consumption behaviour. A questionnaire-based survey (N=411) is conducted by the researcher, and PLS-SEM is used to analyse the data. All hypotheses of the study are supported by the data of the study. The findings contribute to a major theoretical implication where results show that even in the absence of the cognitive response, attitude is still formed to a great extent through affective, behavioural, and normative responses. In terms of practical contribution, marketers should focus on how sustainable consumption behaviours are beneficial to oneself, and more communication emphasis should be placed on females as they play a major role in influencing others in practicing sustainable consumption behaviour. Detailed theoretical and practical contributions of the study are illustrated in concluding part of the thesis.